A modified constitutive model for tensile deformation of 9%Cr steel under prior fatigue loading. (September 2019) - Zhang, Wei; Wang, Xiaowei; Chen, Haofeng; Zhang, Tianyu; Gong, Jianming
Highlights: A strain hardening rule combined with a defined fatigue damage parameter is introduced to represent prior fatigue damage. The proposed model is capable of capturing effects of various prior fatigue loadings. Satisfactory prediction of various tensile deformations is achieved. Abstract: Reliable constitutive models are necessary for the precise design and manufacture of complicated components. This study is devoted to developing a modified constitutive model to capture the effects of prior fatigue loading on subsequent tensile deformation of 9%Cr steel. In the proposed model, a strain hardening rule combined with a defined fatigue damage parameter was introduced to represent prior fatigue damage. The defined fatigue damage parameter based on the inelastic strain range of each cycle is capable of describing the evolution of tensile strength, recovery of martensite laths and decline of dislocation density, regardless of the variation in fatigue loading conditions. To validate the predictive capacity of the proposed model, experimental tensile results at different strain amplitudes, lifetime fractions and hold times of prior fatigue loading were compared with the predicted results. Good agreement between experimental and predicted results indicates that the proposed model is robust in describing the tensile behaviour under prior fatigue loading. Moreover, few determined material parameters are required, which makes the proposed model convenient for practical applications.